Hubungan Antara Work Family Conflict dengan Stres Kerja Perawat di RSUD Cilacap: The Relationship Between Work Family Conflict and Nurse Work Stress at Cilacap Hospital - Shindy Ayuning Prahesti Shindy; Indri Heri Susanti; Fauziah Hanum (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2023)
Nursing is a profession that plays an important role in providing health services. A nurse must fulfill his duties and responsibilities. In carrying out this task, one of them causes stress and the most common cause is headaches (49%) (Ika Puspitasari & Suprayitno, 2021). This is called dual role conflict or work-family conflict. The prevalence of work-family conflict is 83.33% for female nurses and 16.67% for male nurses (Rosyad, 2017). This research aims to determine the relationship between work-family conflict and the work stress of nurses at Cilacap Regional Hospital. This research uses quantitative methods and uses a cross-sectional approach. The sampling method is purposive sampling. The sample was 58 nurses at Cilacap Regional Hospital. Data collection methods used the American Institute of Stress questionnaire and the standard work-family conflict questionnaire adapted from Frone et al. The research results showed that 53 respondents (91.4%) experienced work-family conflict, and 30 respondents (51.7%) experienced work stress, thus there is a significant relationship between work-family conflict and work stress in nurses at Cilacap Regional Hospital with p-value = 0.000 where p < value a (0.05), with r = 0.579. Based on the research results, it is hoped that work-family conflicts faced by female nurses can be achieved by holding family gatherings and providing rewards for high-achieving employees so that work stress is reduced. ABSTRAK Keperawatan merupakan salah satu profesi yang memegang peranan penting dalam memberikan pelayanan kesehatan. Seorang perawat memiliki kewajiban untuk memenuhi tugas dan tanggung jawabnya. Dalam melakukan tugas ini, salah satunya menyebabkan stres dan penyebab paling umum adalah sakit kepala (49%) (Ika Puspitasari & Suprayitno, 2021). Hal ini disebut dengan konflik peran ganda atau work family conflict. Jumlah pravelensi work family conflict presentase perawat wanita 83,33% dan perawat pria 16,67% (Rosyad, 2017). Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara work family conflict dengan stres kerja perawat di RSUD Cilacap. Penelitian ini menggunakan metode kuantitatif dan menggunakan pendekatan cross sectional. Cara pengambilan sampel berupa purposive sampling. Sampel sebanyak 58 perawat di RSUD Cilacap. Metode pengumpulan data menggunakan kuesioner American Institute of stress dan kuesioner baku work family conflict yang diadaptasi dari frone et al. Hasil Penelitian menunjukkan bahwa 53 responden (91,4%) mengalami work family conflict, 30 responden (51,7%) mengalami stres kerja, dengan demikian terdapat hubungan yang signifikan antara work family conflict dengan stres kerja pada perawat di RSUD Cilacap dengan p-value = 0.000 dimana p < nilai a (0.05), dengan r = 0.579. Berdasarkan hasil penelitian diharapkan work family conflict yang dihadapi perawat wanita dapat dengan menyelenggarakan family gathering dan pemberian reward bagi karyawan berprestasi agar stress kerjanya berkurang.